Analysis of MESSENGER high‐resolution images of Mercury's hollows and implications for hollow formation. Issue 9 (30th September 2016) - Blewett, David T.; Stadermann, Amanda C.; Susorney, Hannah C.; Ernst, Carolyn M.; Xiao, Zhiyong; Chabot, Nancy L.; Denevi, Brett W.; Murchie, Scott L.; McCubbin, Francis M.; Kinczyk, Mallory J.; Gillis‐Davis, Jeffrey J.; Solomon, Sean C.
Abstract: High‐resolution images from MESSENGER provide morphological information on the nature and origin of Mercury's hollows, small depressions that likely formed when a volatile constituent was lost from the surface. Because graphite may be a component of the low‐reflectance material that hosts hollows, we suggest that loss of carbon by ion sputtering or conversion to methane by proton irradiation could contribute to hollows formation. Measurements of widespread hollows in 565 images with pixel scales <20 m indicate that the average depth of hollows is 24 ± 16 m. We propose that hollows cease to increase in depth when a volatile‐depleted lag deposit becomes sufficiently thick to protect the underlying surface. The difficulty of developing a lag on steep topography may account for the common occurrence of hollows on crater central peaks and walls. Disruption of the lag, e.g., by secondary cratering, could restart growth of hollows in a location that had been dormant. Images at extremely high resolution (~3 m/pixel) show that the edges of hollows are straight, as expected if the margins formed by scarp retreat. These highest‐resolution images reveal no superposed impact craters, implying that hollows are very young. The width of hollows within rayed crater Balanchine suggests that the maximum time for lateral growth by 1 cm is ~10, 000 yr. A process other than entrainment of dust by gases evolved in a steady‐state sublimation‐like process is likely required to explain the high‐reflectance haloes that surround many hollows. Key Points: Average depth of 2518 hollows in 552 high‐resolution images of Mercury is 24 ± 16 m Hollows enlarge by scarp retreat and cease to deepen when a devolatilized lag becomes thick enough to prevent further volatile loss Carbon could be lost from Mercury's surface via ion sputtering or conversion of graphite to methane by proton bombardment